2018
DOI: 10.1002/cssc.201801810
|View full text |Cite
|
Sign up to set email alerts
|

An Intriguing Pea‐Like Nanostructure of Cobalt Phosphide on Molybdenum Carbide Incorporated Nitrogen‐Doped Carbon Nanosheets for Efficient Electrochemical Water Splitting

Abstract: The development of noble-metal-free, efficient, electrochemical, water-splitting catalyst systems has attracted considerable attention in recent times. In this study, a metal-organic framework based synthetic route to couple two non-noble-metal-based catalysts, CoP and Mo C, supported on nitrogen-doped carbon has been developed. The strategy enables the formation of a nanohybrid with an attractive pea-like morphology, in which spherical CoP particles (≈10 nm) are embedded on two-dimensional nitrogen-doped carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 88 publications
(166 reference statements)
0
36
0
Order By: Relevance
“…Electrochemical splitting of water into molecular hydrogen and oxygen (2H 2 O→O 2 +2H 2 ) is one of the most promising schemes for the sustainable production of clean and renewable fuel such as hydrogen . It is highly desirable to use renewable energy sources to split water into its elemental constituents which can also be lined in with CO 2 capture and conversion (a major environmental pollutant) into storable carbon‐neutral fuels .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical splitting of water into molecular hydrogen and oxygen (2H 2 O→O 2 +2H 2 ) is one of the most promising schemes for the sustainable production of clean and renewable fuel such as hydrogen . It is highly desirable to use renewable energy sources to split water into its elemental constituents which can also be lined in with CO 2 capture and conversion (a major environmental pollutant) into storable carbon‐neutral fuels .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from N-CNTs, nitrogen-doped carbon materials (N-CNMs), including carbon nanosheets, were applied for the OER. At the same time, materials based on molybdenum carbide combined with N-CNMs are usually doped with other transition metals, such as cobalt [99,100] and cobalt phosphide [101]. For instance, Zhu X. et al [102] reported cobalt-doped β-molybdenum carbide encapsulated within nitrogen-doped carbon (Co 0.1 -βMo 2 C@NC), which showed superior catalytic activity toward OER.…”
Section: Molybdenum Carbidementioning
confidence: 99%
“…This coupling strategy has been mainly applied to design bi‐functional electrode with nanostructure engineering of hybrids. Recently, our group has reported intriguing pea‐like nanohybrid structure of CoP−Mo 2 C derived from metal organic framework . Although Mo 2 C is one of the best HER catalyst, it exhibits a relatively poor OER activity.…”
Section: Self‐supported Bifunctional Oer and Her Catalystmentioning
confidence: 99%